Nata De Coco Training for Villagers of Wangon Banyumas District - Restu Frida Utami; Putri Dwi Cahyani (Kontribusia : Research Dissemination for Community Development, 2018)
IbM entitled "Training Nata De Coco for Communities in Rural Wangon, Banyumas" is aimed to assist partners in solving the problems concerning the use of the coconut water and a lack of knowledge and skills of the communities in Wangon in the use of appropriate technologies for coconut water processing into food products named as Nata De Coco nutritious and high economic value product. This community engagement is purposed to: 1). encourages partners to utilize coconut water which has a lower sale value, 2). give briefing, training and skills for partners in the utilization of appropriate technology for coconut water processing into food products that are nutritious Nata De Coco and high economic value. IbM activity is done by providing training that includes some activities: 1) exposure of the material, 2) giving an example of making Nata De Coco, 3). practice of making Nata directly by the participants. Partners who attended the event IbM is household villagers of Wangon, Banyumas. Attendees were women who belonged to the productive age, but they are simply a housewife. From the implementation of IbMactivity, it can be concluded that the participants’ awareness and knowledge about the use of coconut water, and procedure of knowledge of making Nata De Coco are increased